Pengembangan Modul Pembelajaran Audio Visual dengan Teknik Lagu untuk Siswa Kelas X SMAN 1 Muara Jambi pada Materi Sistem Periodik Unsur - Ilsya Martini; Risnita Risnita; Rayandra Asyhar (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2015)
Research and this development is resulted interactive module to design materials the Elements of Periodic System to improve students’ understanding by the concept of materials the Elements of Periodic System. Using the result of the development of materials the Elements of Periodic System makes effective learning base on responsiveness and knowledge of students. To test the feasibility this Audio-Visual Modules made on the basis of expert validation and testing of products in Grade Ten Science Class. Research and development of audio-visual modules by using this song technique is adapted from Lee & Owens with grooves Analysis, Design, Development, Implementation, and Evaluation. The result of tests on the large groups, the skill of the students increased from 74.50 to 88.50 equal with 12%. The result of interviews showed that students responded very positively for an increased understanding by using song technique.